Social Media “Bali Clarify” as an Antidote to Hoaxes in Pandemic of Covid-19 - Agus Ari Iswara; Ajeng Larasati (Jurnal Pekommas, 2021)
The pandemic of the Covid-19 Virus was used by hoax producers as momentum to spread false information. It has also happened in Bali Province. All parties must cooperate to stop the spread of hoaxes and additional media were needed to verify the correctness of the information and convey facts to the public. This research examined the category of hoaxes related to Covid-19 and the use of the “Bali Carify” social media account as a medium for publishing fact-checking results as well as educating the public about the 7 categories of hoaxes. This research used two data sources: reports were released by Bali Province Office of Communication, Information, and Statistic (Diskominfos) and social media monitoring results. Data collection techniques use secondary data in the form of journals, books, and mass media that were relevant to the problems in the study. The object of this research was hoaxes related to Covid-19. This research applied the theory of classification hoaxes into seven categories and theory to verify the correctness of the information. Data analysis was performed inductively.  The data period was limited to only from January to June 2020 (six months). From 14 samples of hoax data that content was related to the Covid-19 phenomenon in Bali, one data was taken that can represent the hoax in the specified category. The results found that there were six categories of hoaxes circulating in Bali, namely parody, misleading content, fake content, fake content, false context, and manipulated content.